Patient-reported outcomes after surgery for endometrial carcinoma: Prevalence of lower-extremity lymphedema after sentinel lymph node mapping versus lymphadenectomy - Leitao, Mario M.; Zhou, Qin C.; Gomez-Hidalgo, Natalia R.; Iasonos, Alexia; Baser, Ray; Mezzancello, Marissa; Chang, Kaity; Ward, Jae; Chi, Dennis S.; Long Roche, Kara; Sonoda, Yukio; Brown, Carol L.; et al. (Gynecologic oncology, 2020)
To compare the prevalence of patient-reported lower-extremity lymphedema (LEL) with sentinel lymph node (SLN) mapping versus comprehensive lymph node dissection (LND) for the surgical management of newly diagnosed endometrial carcinoma. Patients who underwent primary surgery for endometrial cancer from 01/2006-12/2012 were mailed a survey that included a validated 13-item LEL screening questionnaire in 08/2016. Patients diagnosed with LEL prior to surgery and those who answered ≤6 survey items were excluded. Of 1275 potential participants, 623 (49%) responded to the survey and 599 were evaluable (180 SLN, 352 LND, 67 hysterectomy alone). Median BMI was similar among cohorts (P = 0.99). External-beam radiation therapy (EBRT) was used in 10/180 (5.5%) SLN and 35/352 (10%) LND patients (P = 0.1). Self-reported LEL prevalence was 27% (49/180) and 41% (144/352), respectively (OR, 1.85; 95% CI, 1.25–2.74; P = 0.002). LEL prevalence was 51% (23/45) in patients who received EBRT and 35% (170/487) in those who did not (OR, 1.95; 95% CI, 1.06–3.6; P = 0.03). High BMI was associated with increased prevalence of LEL (OR, 1.04; 95% CI, 1.02–1.06; P = 0.001). After controlling for EBRT and BMI, LND retained independent association with an increased prevalence of LEL over SLN (OR, 1.8; 95% CI, 1.22–2.69; P = 0.003). Patients with self-reported LEL had significantly worse QOL compared to those without self-reported LEL. This is the first study to assess patient-reported LEL after SLN mapping for endometrial cancer. SLN mapping was independently associated with a significantly lower prevalence of patient-reported LEL. High BMI and adjuvant EBRT were associated with an increased prevalence of patient-reported LEL. •SLN mapping was independently associated with significantly lower rate of patient-reported lower extremity lymphedema (LEL).•Increasing BMI and use of adjuvant EBRT were associated with an increased prevalence of patient-reported LEL.•SLN mapping in the surgical management of newly diagnosed endometrial cancer may spare these patients from LEL.•Survival outcomes were similar between SLN mapping and comprehensive lymphadenectomy after endometrial cancer surgery.